Opini Publik tentang Malpraktek Kedokteran - Hardisman Hardisman (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: In providing services, medical professionals have to be aware of social norms, ethics and laws. Behaviors violate those regulations attract public attention and can lead to medical malpractice allegations. This study aimed to explore public opinion on medical malpractice, which was analyzed base on medical ethic principles.Method: To answer the research question, descriptive and qualitative online survey had been conducted from November 2009 to October 2010, which used structured and open-ended questionnaire. The participants were obtained by employing non-probability convenience sampling. Later, the quantitative data was analyzed descriptively, and the qualitative data was analyzed thematically and presented narratively.Results: In general, public opinion on malpractice is similar to the principles of medical ethics. They believe that wrong procedures, diagnosis and treatments are factors of the malpractice. However, the participants adopt more consequentialism philosophy, which emphasize on outcome of patients and lack of consideration what the doctors has done base on medical standards. More over, participants’ explanations on medical malpractice reflect dissatisfaction of medical services which may due to low quality of information and attitude of doctors and other staffs in providing services.Conclusion: To improve public opinion on medical service and prevent medical malpractice allegation, doctors and other staffs have to obey professional standards and ethics, providing adequate information and good communication.